Clinical anatomy and physiology of the visual system - Remington, Lee Ann
Providing the ocular anatomy and physiology content needed for a thorough comprehension of this complex field, Clinical Anatomy and Physiology of the Visual System, 4th Edition, offers a solid foundation for recognizing and understanding specific clinical situations and how they relate to anatomic structure. This concise, well-referenced resource covers the clinical anatomy of the eye, its adnexa and visual pathways, and histologic information—the information you need for success in coursework, certification exams, and clinical practice.